Essentials of life-span development - Santrock, John W. (McGraw-Hill LLC, 2022)
"Essentials of Life-Span Development, 7e" allows students to study whenever, wherever, and however they choose. Regardless of individual study habits, preparation, and approaches to the course, Essentials connects with students on a personal, individual basis and provides a road map for success in the course"--Provided by publisher.